Description of the larva and pupa of Potamyia phaidra Malicky and Chantaramongkol (Trichoptera: Hydropsychidae) from southern Thailand - Prommi, Taeng On; Permkam, Surakrai; Sites, Robert W. (Zootaxa, 2006)
Larvae and pupae of Potamyia phaidra Malicky and Chantaramongkol (Trichoptera: Hydropsychidae) were collected from montane streams in southern Thailand. Pupal identifications were based on genitalic features in common with described adults, and larvae were associated with the pupae. Herein, the final larval instar and pupa are described, diagnosed, and figured.